Criminology, crime and criminal justice in Croatia - Getoš, Anna-Maria (European journal of criminology, 2017)
Criminology and in more general terms ‘crime research’ have a very long tradition in Croatia, dating back in terms of formal institutionalization as far as 1906, when the Chair for Criminal-Complementary Sciences and Sociology at the Zagreb Faculty of Law was established. Despite criminology’s long institutional tradition in Croatia, criminology as a serious and independent research discipline started rather late to take off in Croatia in a systematic manner. The article presents basic facts and figures about Croatian criminology, crime and criminal justice, providing a solid overview of the complex country situation, which is still struggling with many transitional challenges. Croatia, like many other countries in the region, does not seem to have a ‘conventional crime problem’ and does not fit the profile of a ‘high crime region’ when compared with the rest of Europe, but it struggles with corruption and organized crime, and it still has to deal with atrocious crimes from the recent past and the far-reaching consequences of war profiteering and criminal ‘privatization’.